Сardioprotective agents with biaromatic structure. Part 6. Beta blockers - G. V. Mokrov (LLC "Publisher OKI", 2023)
β-Blockers are one of the oldest classes of cardioprotectors used in the treatment of cardiovascular diseases. They reduce the heart rate, have a hypotensive eﬀect, inhibit myocardial contractility and have antiarrhythmic properties. In the series of biaromatic compounds with a linear linker, there is a quite large group of β-blockers, which in addition to two aromatic nuclei contain a 1,2-dihydroxy-3-aminopropane fragment in the linker, that is the key for the presence of β-blocking activity. Among the compounds of this group are widely used drugs nebivolol and carvedilol, which are used in the treatment of chronic heart failure and arterial hypertension.